The importance of metacognition and the experiential learning process within a cultural intelligence–based approach to cross-cultural coaching - Catherine A. van der Horst; Ruth M. Albertyn (SA Journal of Human Resource Management, 2018)
Orientation: Research on cultural intelligence (CQ) is increasingly used to evaluate, explain and predict the cross-cultural efficacy of management behaviour in everyday cross-cultural interactions. However, there is limited evidence in cross-cultural coaching of the use of a CQ-based approach incorporating metacognition and experiential learning theory (ELT).